Phase Characteristics of Models of GaAs Gyroelectric Waveguides with Temperature Sensitive Anisotropic Dielectric Layers in Case of One Layer - Plonis Darius; Katkevičius Andrius; Belova-Plonienė Diana (Electrical, Control and Communication Engineering, 2018)
Models of open cylindrical multilayer gyroelectric-anisotropic-gyroelectric waveguides are presented in this paper. The influence of density of free carriers, temperature and the presence of the external dielectric layer on the wave phase characteristics of the models of n-GaAs waveguides has been evaluated. Differential Maxwell’s equations, coupled mode and partial area methods have been used to obtain complex dispersion equation of the models of gyroelectric-anisotropic-gyroelectric waveguides with or without the temperature sensitive external anisotropic dielectric layer. The analysis has shown that the phase characteristics are practically unchanged when the density of electrons is equal to N = (1017–5·1018) m−3, d/rs = 0, the changes of wave phase coefficients are obtained in the models of waveguides with the external anisotropic dielectric layer. The largest differences of wave phase coefficient are obtained when the density of electrons is N = 1021 m−3. The external dielectric layer improves the control of gyroelectric n-GaAs waveguides with temperature.